Dos especies de Ambrosia (Compositae, Heliantheae) adventicias en el centro de México - Rzedowski, Jerzy; Calderon de Rzedowski, Graciela (Instituto de Ecología, A.C., 1998)
Ambrosia camphorata (Greene) Payne and A. cordifolia (A. Gray) Payne reveal a remarkable disjunct distribution. Both are members of the flora of large areas of the Sonoran arid zone and also grow in a relatively limited portion of the states of San Luis Potosí, Guanajuato and Querétaro. In view of the fact that the center of diversity and of probable origin of this group of plants is localized in northwestern Mexico and on account of their apparent behavior as invasors in the central part of the country, it is believed that these species should have arrived in the latter region in relatively recent times. The XIX century is postulated as a possible epoch of their migratory movement.